The Evolution of Family Law in Luxembourg in the Era of Globalization - Tamrin Fathoni; Achen Karriel (Edujavare Publishing, 2026)
This study analyzes the evolution of family law in Luxembourg in the era of globalization. The research aims to examine how globalization influences legal transformation in family law, particularly in terms of legal recognition of diverse family forms, gender equality, and cross-border family relations. A normative legal research method is used with conceptual, statutory, and comparative approaches based on secondary legal materials, including legislation, EU regulations, academic literature, and judicial decisions. The findings indicate that Luxembourg family law has evolved significantly under the influence of European integration and international human rights standards, particularly through the recognition of registered partnerships, same-sex relationships, and liberalized divorce regulations. However, challenges remain in balancing traditional legal values, national sovereignty, and supranational legal influence. The study concludes that globalization has played a transformative role in shaping a more inclusive and human rights–based family law system in Luxembourg.